Pre-trial detention and reasonable time in the Brazilian Superior Courts’ jurisprudence - Daiana Santos Ryu (Revista Brasileira de Direito Processual Penal)
Being the pre-trial detention the most severe precautionary measure and considering that the Judiciary has been trivializing its application, by totalizing approximately 40% of provisional prisoners in prisons custody, this present research aims to analyze the Superior Courts decisions when deliberating about the reasonableness of the precautionary prison. In conclusion, it is intended to expose how the precautionary prison duration has been deliberated on writs judgment, analyzing its content, along with the method applied when computing the precautionary prison term reasonableness. According to the statistics presented, the national Superior Courts demonstrate propensity on maintaining extended provisional prison by using generic assertion, validating the precautionary prison significant rate in Brazil.